Anthropogenic impacts on the contextual morphological diversification and adaptation of Nile tilapia (Oreochromis niloticus, L. 1758) in East Africa - Dias Tibihika, Papius; Waidbacher, Herwig; Masembe, Charles; Curto, Manuel; Sabatino, Stephen; Alemayehu, Esayas; Meulenbroek, Paul; Akoll, Peter; Meimberg, Harald (Environmental Biology of Fishes, 2018)
Nile tilapia occurs naturally in East Africa where it’s an economically important species. Many of the natural populations of Nile tilapia have been affected by anthropogenic activities including translocations, associated with programmes aimed at enhancing capture fisheries and aquaculture productivity. Using geometric morphometric analyses, we tested the hypothesis that such anthropogenic activities have augmented admixture among natural populations of Nile tilapia and influenced the geographical distribution of morphological variation within the species. Our expectation was that Nile tilapia shape divergent might be consistent with reportedly anthropogenic activities in nonnative environments. To test this hypothesis, we analyzed the shapes of 490 individuals from thirteen populations; three farms, six natives and four nonnative natural populations. Our analysis revealed that the most pronounced shape diversification was observed in seven populations; three nonnatives (Victoria, Kyoga and Sindi farm) and four natives (Albert, River Nile, George and Turkana). The features responsible for the observed morphotypes were mainly related to the orientation of the anterior region of the fish and may be due to diversifying selection in response to new environmental pressures (for nonnative populations), admixture or drift. Shape change in the nonnative high-altitude populations was unexpectedly conserved, suggesting recent introductions which may have not resulted in admixture or there was strong selection against change in the traits measured. On the other hand, the recorded morphotypic clusters explained the possible genetic link to their putative ancestral home. Our results were partially consistent with our prediction that the nonnative populations exhibited divergent morphotypes. We recommend further investigations with molecular genetics for followup of these findings.
Keywords: Nile tilapia; Geometric morphometrics; MorphoJ; Populations; Condition factor; Morphological diversification